Mind the gap: exploring stakeholder perspectives on police-led pathways to crisis mental health care for young people in Ireland - Rooney, Louise (Policing and society, 2024)
Over the past few decades, the level of police involvement at a community level in matters of mental health has increased significantly. Police are often the only agency immediately available day or night to respond to such emergencies and are often left to deal with mental illness and associated social crises with very limited support. Whilst recent years have witnessed an upsurge in governmental policy intended to safeguard vulnerable groups, such as young people and people with mental illness, there is a dearth of research regarding the proficiency and operability of these directives in practice. Even less is known about how these policies are practically applied to young people in crisis. The study examines the police-led care pathways of Irish youth experiencing a crisis mental health event from the commencement of police involvement through to the initiation of psychiatric care. Qualitative interviews were conducted with police and a group of stakeholders comprised of medical professionals and a social worker. Results indicate a complex care pathway beset with ambiguous policy and legislation, deficits in specialist training, and chronic under-resourcing of services. In the face of these shortcomings, police innovate informal practices that sometimes help and at other times pose a risk to young people in crisis. Furthermore, uncertainties surrounding formal procedure was a source of significant psychological burden for police and potential disciplinary action. These findings are discussed in the context of existing theory and research, and recommendations for policy and practice are offered.